SOME BIOLOGICAL CHARACTERISTICS OF LONGTAIL TUNA CAUGHT IN THE SEA WATERS OF KHANH HOA PROVINCE - Phuoc, Tran Van (Vietnam Journal of Marine Science and Technology, 2008)
Based on date from length and weight measurements of 218 Longtail tuna samples in the seawaters of Khanh Hoa province. Fork lenght range was from 31 to 49 cm, average 39.13 cm and 40 - 44 cm fork lenght group comprised 39.45%. Weight range was form 550 to 2000 g, average 1090 g and 1250 - 1400 g weight group comprised 19.72%. The Lenght - Weight relationship equation, W = 0.000063L2.7882, R2 = 0.8436; the growth parameters of the Von Bertalanffy equation, Lt = 51.98 (1 – e-0.22t); the total lenght - fork lenght relation equation, Lt = 1.0439Lf + 1.149, R2 = 0.9603. In this research period, 99.3% of both sex having gonads belonged to stage I and II (maturity). Degree of fullness of stomach was very poor - degree of fullness 1, 2 and 3 comprised 87.01% and major species of preys found in stomach of Longtail tuna were major fish, squid and shrimp.